Defect states contributed nanoscale contact electrification at ZnO nanowires packed film surfaces. (January 2021) - Song, Yiding; Wang, Nan; Fadlallah, Mohamed M.; Tao, Shuxia; Yang, Ya; Wang, Zhong Lin
Abstract: Efficient conversion of mechanical energy in our surrounding environment into electric power has become a promising strategy for meeting the ever-increasing energy consumption of small and distributed electronics. The contact-electrification-based triboelectric nanogenerators are one of the emerging devices to achieve such energy conversion. However, conventional contact electrifications between two insulators are limited by their low current density and alternating current output. Here we report a nanoscale contact electrification induced direct current output based on the flow of electrons from the defect states of the ZnO nanowires-packed film to the contact sliding conductive AFM tip. Combining experimental materials characterization and density functional theory (DFT) calculations, the direct current output is closely related to the concentration of oxygen vacancy defect states on the surface of ZnO nanowires: the higher the oxygen vacancy concentration, the higher the current output. Under optimized conditions, we obtain an ultrahigh current density of 10 8 A m -2, which is several orders of magnitude higher than that of the conventional contact electrification and other effects. This work provides a new route of utilizing defect states contributed contact electrification for realizing nanoscale mechanical energy scavenging. Graphical abstract: Efficient conversion of mechanical energy in our surrounding environment into electric power has become a promising strategy for meeting the ever-increasing energy consumption of small and distributed electronics. The contact-electrification-based triboelectric nanogenerators are one of the emerging devices to achieve such energy conversion. However, conventional contact electrifications between two insulators are limited by their low current density and alternating current output. Here we report a nanoscale contact electrification induced direct current output based on the flow of electrons from the defect states of the ZnO nanowires-packed film to the contact sliding conductive AFM tip. Combining experimental materials characterization and density functional theory (DFT) calculations, the direct current output is closely related to the concentration of oxygen vacancy defect states on the surface of ZnO nanowires: the higher the oxygen vacancy concentration, the higher the current output. Under optimized conditions, we obtain an ultrahigh current density of 10 8 A m -2, which is several orders of magnitude higher than that of the conventional contact electrification and other effects. This work provides a new route of utilizing defect states contributed contact electrification for realizing nanoscale mechanical energy scavenging. Image 1 Highlights: We report a defect states contributed nanoscale contact electrification induced direct current output. The DC output exhibits an ultrahigh high current density in the order of 10 8 A m -2 . The direct current output is closely related to the concentration of oxygen vacancy defect states on the surface.